Clinico-demographic profile of HIV patients at ART centre of a tertiary care referral hospital in North India - Kumari, Rashmi; Kumar, Mritunjay; Mohapatra, S. C. (International Journal Of Community Medicine And Public Health, 2017)
Background: According to the National AIDS Control Organization (NACO), HIV prevalence in India is 0.36% and people living with HIV are around 2.47 million. Although antiretroviral treatment (ART) does not cure HIV/AIDS, but effective ART regimens inhibit the efficient replication of the HIV virus, and reduce viremia to undetectable levels. Methods: HIV positive patients qualified to be enrolled in to the study were those who attended the infectious diseases clinic at least twice (one follow-up visit at least six months apart), between January 2009 to December 2011. The protocol was approved by the Ethical Committee of the IMS, BHU. History and detail of patients were recorded on a pre-designed performa which included the socio-demographic profile of the patients, mode of transmission, presenting symptoms, opportunistic infections and many others. Results: 5308 HIV positive patients were registered during three year of study period at the ART Centre of IMS, BHU. Of these 3379 (63.7%) were males and 1929 (36.3%) were females. Heterosexual mode of transmission was commonest in the study group and amounted to 70.5% of total HIV patients on ART. Pulmonary tuberculosis was most common opportunistic infection and was present in 1045(19.7%) of patients on ART. CD4 counts of the patients were significantly inversely correlated with the number of symptoms and the number of opportunistic infections. Conclusions: HIV infection is one of the major infectious diseases in this part of India, and being chronic and lifelong in nature, its impact is huge compared to other infectious diseases. People with high risk behavior and the spouse of the affected couple need to be educated for primary and secondary prevention of the disease.